Papers - Relation between Plastic Deformation in Deep Drawing and Tensile Properties of Various Metals - M. H. Sommer (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1934)
Many attempts have been made to develop a relation between the tensile properties and the deep-stamping qualities of metals commonly used in deep drawing. These operations are generally performed cold and the metal is always stressed beyond the elastic limit. However, the problem cannot be readily solved without a proper investigation of: (1) the relation between actual stress and actual strain in the plastic range and (2) the stresses that are set up in the metal during the process of deep stamping. Much work has been done in recent years to add to our knowledge on plastic deformation of metals and the shortcomings of the ordinary tensile test, particularly in the plastic range, have been sufficiently recognized. It has been widely acknowledged that the local contraction, which appears in a tensile test after the maximum load is reached, is not a general characteristic of the material but is peculiar to this form of testing. The plastic deformation of materials is explained by the slip of their crystals along certain planes and this rearrangement should be similar whether observed in a tensile, compression or torsion test, and if the results of any of these forms of testing show deviations, it must be due to other influences, as for example the local contraction in a tensile test. For this reason the tensile-test curve as obtained from the measurements taken on a tensile-test machine or registered by an autographic device has been supplemented by the so-called "actual stress-strain curve," which is constructed from the observed tensile-test data by eliminating the effect of local contraction and is in complete alignment with the stress-strain values obtained in a compresison or torsion test. The actual stress-strain curve shows the increase of actual unit stress in relation to unit elongation beyond the yield point and beyond the point of maximum load and indicates clearly the extent of strain-hardening which the ordinary tensile-test curve does not reveal. The following metals have been investigated in this paper and their actual stress-strain curves and, further, their char-